Uniparental isodisomy of chromosome 1 results in glycogen storage disease type III with profound growth retardation. Issue 5 (27th March 2019) - Ponzi, Emanuela; Alesi, Viola; Lepri, Francesca R.; Genovese, Silvia; Loddo, Sara; Mucciolo, Mafalda; Novelli, Antonio; Dionisi‐Vici, Carlo; Maiorana, Arianna
Abstract: Background: Glycogen storage disease type III (GSDIII) is caused by mutations of AGL gene with debranching enzyme deficiency. Patients with GSDIII manifest fasting hypoglycemia, hepatomegaly, hepatopathy, myopathy, and cardiomyopathy. We report on an 18‐year‐old boy with a profound growth retardation (<3 SD ) besides typical clinical features of GSDIII, whereby endocrinological studies were negative. Methods and Results: Molecular analysis of AGL gene revealed the homozygous reported variant c.3903_3904insA. Since discordant results from segregation studies showed the carrier status in one parent only, SNP array and short tandem repeats analyses were performed, revealing a paternal disomy of chromosome 1 (UPD1). Conclusion: This study describes the first case of GSDIII resulting from UPD1. UPD can play an important role even in case of imprinted genes. DIRAS3 is a maternally imprinted tumor suppressor gene, located on chromosome 1p31, and implicated in growth and oncogenesis. It can be speculated that DIRAS3 overexpression might have a role in the severe short stature of our patient. The study emphasizes the importance of parental segregation analysis especially in patients with recessive conditions to look for specific genetic causes of disease and to estimate properly the risk of family recurrence. Abstract : The work describes the first case of glycogen storage disease type III with severe growth retardation, resulting from uniparental disomy of chromosome 1, with imprinted tumor suppressor gene implicated in growth. The study highlights the importance of segregation studies to look for specific genetic causes of disease.